Splendors and glooms eaudiobook - Schlitz, Laura Amy (Recorded Books Inc., 2012)
Newbery Medal-winning author Laura Amy Schlitz has garnered starred reviews and popular acclaim for her Victorian gothic thriller Splendors and Glooms. When Clara Wintermute, the only child of a wealthy doctor, pleads that mas-ter puppeteer Gaspare Grisini perform at her birthday party, she unwittingly places herself in the utmost peril. After Clara disappears the night of the show, Grisini's innocent assistants attempt to locate the missing birthday girl- but dark and terrifying forces await.